MARKETING 5.0 : PERAN KEY OPINION LEADER DAN TRUSTWORTHINESS TERHADAP CUSTOMER ENGAGEMENT SCARLETT WHITENING - Khumaeroh, Luk Lu'ul; Fauzi, Irsal (STIE AMA Salatiga, 2025)
Abstrac : This research aims to analyze the influence of Key Opinion Leader (KOL) and Trustworthiness on Customer Engagement in Scarlett Whitening products, with Purchase Intention as a mediating variable. This research uses quantitative methods with an explanatory research approach to explain the causal relationship between the variables studied. Data collection was carried out through a survey of 96 respondents who were users of Scarlett Whitening products in Ungaran, Semarang Regency, using a purposive sampling technique. The data analysis technique uses Partial Least Square (PLS). The research results show that Key Opinion Leaders do not have a significant influence on Customer Engagement or Purchase Intention directly. However, a significant influence was found through the mediation of Purchase Intention. On the other hand, Trustworthiness has a significant direct influence on both Customer Engagement and Purchase Intention. Apart from that, Trustworthiness also has an indirect influence on Customer Engagement through Purchase Intention. This research highlights the importance of consumer trust as a key factor in increasing customer engagement and driving purchase intent. Scarlett Whitening is advised to strengthen the Trustworthiness element and evaluate strategies for selecting and using KOLs to make them more relevant to the target market.Abstrak : Penelitian ini bertujuan untuk menganalisis pengaruh Key Opinion Leader (KOL) dan Trustworthiness terhadap Customer Engagement pada produk Scarlett Whitening, dengan Purchase Intention sebagai variabel mediasi. Penelitian ini menggunakan metode kuantitatif dengan pendekatan explanatory research untuk menjelaskan hubungan kausal antara variabel-variabel yang diteliti. Pengumpulan data dilakukan melalui survei terhadap 96 responden yang merupakan pengguna produk Scarlett Whitening di Ungaran, Kabupaten Semarang, dengan teknik purposive sampling. Teknik analisis data menggunakan Partial Least Square (PLS). Hasil penelitian menunjukkan bahwa Key Opinion Leader tidak memiliki pengaruh signifikan terhadap Customer Engagement maupun Purchase Intention secara langsung. Namun, pengaruh signifikan ditemukan melalui mediasi Purchase Intention. Sebaliknya, Trustworthiness memiliki pengaruh langsung signifikan baik terhadap Customer Engagement maupun Purchase Intention. Selain itu, Trustworthiness juga memiliki pengaruh tidak langsung terhadap Customer Engagement melalui Purchase Intention. Penelitian ini menyoroti pentingnya kepercayaan konsumen sebagai faktor kunci dalam meningkatkan keterlibatan pelanggan dan mendorong niat beli. Scarlett Whitening disarankan untuk memperkuat elemen Trustworthiness serta mengevaluasi strategi pemilihan dan penggunaan KOL agar lebih relevan dengan target pasar.